Covid-19 As Wake-Up Call to Reconsider the Mainstream Financial Practices: Islamic Finance Perspective - Nour Aldeen, Khaled (Journal of Developing Economies, 2021)
This paper aims to present recommendations that can immune a conventional financial system against the global crisis, particularly the Covid-19 pandemic crisis from the lens of Islamic finance. This paper contends that Islamic finance is a relatively immune financial system comparing to the mainstream financial system by eliminating Riba and considering only asset-backed transactions as fruitful ones. This paper begins with the conceptual investigation of the literature on the principles of Islamic finance. The literature's origins include primary sources (Quraan and hadith) and secondary sources (books, journals, and online resources). This paper is only conceptual and does not aim to examine the issues or theories empirically. The article will be useful to develop hypotheses for future research, especially in Islamic finance. Islamic concepts will of interest, especially for countries that adopt the conventional financial system. This paper will also be useful in the introduction for both Islamic and conventional finance practitioners alike. This paper provides a conceptual model to substitute the dominant conventional economics. Highlights the necessary steps to reconsider the conventional financial system. Islamic finance can mitigate the impact of COVID-19 on the economies mainly because of the PLS (profit-loss sharing) system and Islamic ethics in financial transactions. The paper shows its originality in substance and makes a unique contribution to the literature on systems and ethics by emphasizing Islamic finance practices approaching an effective alternative to conventional finance. Keywords: Islamic Finance, Mainstream Finance, Covid-19 JEL: G00, Y9